2018
DOI: 10.7454/hubs.asia.1140818
|View full text |Cite
|
Sign up to set email alerts
|

Palestinian Solidarity Action: The Dynamics of Politicized and Religious Identity Patterns Among Student Activists

Abstract: This study attempted to explain the factors that lead Muslim student activists to participate in Palestinian solidarity actions by testing the Social Identity Model Collective Action model (SIMCA, van Zomeren, Postmes, & Spears, 2008). A survey of 303 student members/administrators of Islamic organizations was conducted. The sample was obtained from more than seven Islamic-based student organizations. Collective solidarity actions were comprised of peaceful actions such as demonstrations, protests, and petitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
6
0
2
Order By: Relevance
“…Our first criterion was that the studies should have included the measures of both social identification and participation in collective action variables. Some studies focusing on the relationship between shared social identity and collective action that took place between 2011 and 2020, were not included in this study, since they were either qualitative (e.g., Khazraee & Novak, 2018), or not digitally mediated (see Selvanathan & Lickel, 2019;Shadiqi et al, 2018).…”
Section: Methods Inclusion Criteria and Literature Searchmentioning
confidence: 99%
“…Our first criterion was that the studies should have included the measures of both social identification and participation in collective action variables. Some studies focusing on the relationship between shared social identity and collective action that took place between 2011 and 2020, were not included in this study, since they were either qualitative (e.g., Khazraee & Novak, 2018), or not digitally mediated (see Selvanathan & Lickel, 2019;Shadiqi et al, 2018).…”
Section: Methods Inclusion Criteria and Literature Searchmentioning
confidence: 99%
“…We explored the role of religious identity in collective action, following the suggestion of Baysu and Phalet (2017). Shadiqi et al, (2018) found that Muslim identity does not directly explain the peaceful collective action in the Palestinian conflict context; instead, group efficacy was determined as one mediating factor between the two. Derived from there, we believe that religious identity could be another factor contributing to such action.…”
Section: Religious Identity In Collective Actionmentioning
confidence: 99%
“…Sekalipun demikian, studi ini menunjukkan bahwa tidak ada korelasi antara persepsi bawahan mengenai agama pemimpin dengan dukungan terhadap pemimpin (leader endorsement). Hasil ini sejalan dengan temuan penelitian sebelumnya, bahwa identitas agama tidak secara langsung memotivasi seseorang di dalam sebuah organisasi untuk berperilaku (Shadiqi, Muluk, & Milla, 2018). Temuan ini kemungkinan menggambarkan bahwa identitas agama dipandang sebagai aspek kehidupan pribadi individu, sehingga pada penelitian ini, terkait dengan teori identitas sosial, persepsi terhadap identitas agama pemimpin bukanlah faktor yang memengaruhi dukungan bawahan kepada pemimpin.…”
Section: Tabel 1 Means Standard Deviations and Correlationsunclassified